Topics in Spinal Anaesthesia - Whizar-Lugo, Victor M. (IntechOpen, 2014)
Topics on Spinal Anaesthesia consists of eight important and updated chapters covering subarachnoid anaesthesia for major orthopaedic surgeries, ambulatory and short stay plastic surgical procedures, complications, and discussing the usefulness of opioids and non opioids drugs as spinal adjuvants to enhance subarachnoid block, transoperative analgesia and postoperative analgesia in various clinical scenarios. InTech invited respectable anesthesiologists from different countries to write this book. The authors and co-authors discussed in detail the advances in these subjects, so that the reader has an updated view and can use this knowledge on his/her patients. It is a practical book covering current information about subarachnoid anaesthesia.